Environmental Literature in Children's Stories: An Analytical Reading of a Selected Sample of Children's Stories (The International Journal for Scientific Research, 2026)
This research aims to study environmental representations in children's stories from the perspective of environmental literary criticism. It seeks to uncover the mechanisms by which narrative storytelling is employed to cultivate environmental awareness in children, and to assess the extent to which these approaches align with the developmental characteristics of the target group. The research stems from a central question: What is the image of the environment in the narrative structure of environmental children's stories? And what are the artistic and intellectual criteria that make environmental stories effective tools for environmental education and the development of ecological awareness?The study adopts a descriptive-analytical approach within the framework of environmental literary criticism. It is based on the hypotheses formulated by Lawrence Bell regarding the representation of the environment in literary texts, emphasizing the presence of the environment as an active entity rather than merely a backdrop. It highlights humanity's ethical responsibility towards the environment and moves beyond anthropocentrism to an awareness of the interplay between human and non-human elements. The study also draws upon the concepts of environmental education and the dimensions of environmental awareness (knowledge, attitude, and behavior) as a framework for evaluating the narrative content. This research analyzed a purposive sample of children's stories addressing contemporary environmental issues to uncover the environmental values ​​embedded within them, the aesthetic and artistic mechanisms employed in their narrative structure (such as event, character, plot, dialogue, and conflict), and their alignment with the age and cognitive characteristics of the child reader. It also examined the nature of the narrative discourse: is it direct and didactic, or does it operate through artistic inclusion and aesthetic shaping?The research concluded that an effective environmental story is one that balances the cognitive, emotional, and behavioral dimensions, presenting the environment as a living, changing entity with which human destiny is organically linked. This is achieved while avoiding didacticism and directness, and relying on artistic techniques that enhance the child's interaction and emotional engagement. Furthermore, the research demonstrated that achieving environmental awareness in children's stories is not accomplished merely by including environmental information, but rather through a coherent narrative structure that stimulates thought, cultivates positive attitudes, and encourages responsible behavior. The scientific value of this research lies in its contribution to establishing a critical environmental approach to Arabic children's literature, linking it to the dimensions of environmental education, and proposing artistic and normative guidelines for environmental narrative writing aimed at children. This strengthens the role of literature in supporting the Sustainable Development Goals and building environmentally conscious citizenship among younger generations.
Keywords: Environmental literature; children's stories; environmental literary criticism; environmental education; environmental awareness; ecological narrative